2017
DOI: 10.1136/bmjqs-2017-006710
|View full text |Cite
|
Sign up to set email alerts
|

Getting back on track: a systematic review of the outcomes of remediation and rehabilitation programmes for healthcare professionals with performance concerns

Abstract: The literature is dominated by outcomes for physicians in North American programmes, with positive outcomes for SUD and varying outcomes for dyscompetence. Based on our findings we cannot make valid comparisons in outcomes between professions and specific performance concerns, and we call for other programmes to report on outcomes for different professions and concerns. Because of the positive outcomes of physician health programmes, other countries should consider introducing similar programmes to support hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Once the extent of misuse by paramedics has been established, evidence-based surveillance and support can be provided. Intervention rather than disciplinary action for practitioners with performance concerns have generally proved to be effective (Ganley et al, 2005;Kunyk et al, 2016;Weenik et al, 2017). This protects patients from harm while ensuring that professionals are supported and do not leave, resulting in reduced staffing, loss of valuable experience and extra costs for training new staff.…”
Section: Occupational and Post-traumatic Stressmentioning
confidence: 99%
“…Once the extent of misuse by paramedics has been established, evidence-based surveillance and support can be provided. Intervention rather than disciplinary action for practitioners with performance concerns have generally proved to be effective (Ganley et al, 2005;Kunyk et al, 2016;Weenik et al, 2017). This protects patients from harm while ensuring that professionals are supported and do not leave, resulting in reduced staffing, loss of valuable experience and extra costs for training new staff.…”
Section: Occupational and Post-traumatic Stressmentioning
confidence: 99%
“…The present article by Weenink et al provides a systematic review of the outcomes of rehabilitation and remediation programmes for healthcare professionals 6. The authors’ systematic review revealed that the literature comes primarily from North America and that many papers reported very positive outcomes for substance abuse programmes.…”
mentioning
confidence: 93%
“…Available data on medical errors, malpractice claims, disciplinary actions and various other sources suggest that between 6% and 12% of physicians meet criteria for ‘dyscompetence’ in the USA 4 5. Elsewhere, the percentage varies according to the data sources 6. In Ontario, for instance, where the data come from randomly selected physicians, it is estimated that approximately 15% of family physicians and 3% of specialists have considerable deficiencies 4 7 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors share this concern, although it is noted that many misdemeanours, especially those related to addiction or substance abuse, may be related to underlying health disorders, 15–17 and as indicated in the survey preamble, any affected individual has a right to both privacy and redemption. The two concepts (disclosure of disability and disclosure of misdemeanour) were both included in the current study not to conflate concepts but because they are both, variably, addressed in registration processes (Table 1) and have been linked in definitions of fitness to practice, which encompass professional conduct and behaviour, freedom from mental or physical impairment and clinical competence 18 .…”
Section: Resultsmentioning
confidence: 99%